2020
DOI: 10.1093/mnras/staa2733
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of dark haloes emerge from their merger histories

Abstract: The concentration parameter is a key characteristic of a dark matter halo that conveniently connects the halo’s present-day structure with its assembly history. Using ‘Dark Sky’, a suite of cosmological N-body simulations, we investigate how halo concentration evolves with time and emerges from the mass assembly history. We also explore the origin of the scatter in the relation between concentration and assembly history. We show that the evolution of halo concentration has two primary modes: (1) smooth increas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 77 publications
12
39
0
Order By: Relevance
“…Since the averaged background density of the Universe drops with time, older halos have usually higher central density and also higher concentrations. For the ΛCDM model this scenario is evident in a wealth of simulations-based studies [26,31,32,106,109].…”
Section: Mass Assembly Historiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the averaged background density of the Universe drops with time, older halos have usually higher central density and also higher concentrations. For the ΛCDM model this scenario is evident in a wealth of simulations-based studies [26,31,32,106,109].…”
Section: Mass Assembly Historiesmentioning
confidence: 97%
“…It was found that the local vorticity and tidal fields play important role in galaxy and halo spin acquisition (both magnitude and direction) (e.g., [18][19][20][21][22][23][24][25][26]). The cosmic web environment affects halos and galaxies in many aspects, from shaping the anisotropic distribution of satellite galaxies [27][28][29], to halo concentrations and their assembly histories [26,[30][31][32], and halo shapes [15,33,34]. The large-scale structure environment correlates also with galaxy stellar mass [35][36][37] and morphological properties [38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…This result implies that our model can approximate halo growth in such a way that residual errors in the fit are uncorrelated with the density field on large scales. This finding is especially interesting in light of the relationship between assembly bias and halo concentration (Wechsler et al 2006), the latter of which is closely connected to assembly history (Wechsler et al 2002;Chen et al 2020b), and is known to be strongly influenced by mergers (e.g., Wang et al 2020). We will investigate this issue systematically in follow-up work to the present paper.…”
Section: Discussion and Future Workmentioning
confidence: 87%
“…The mass density profile of dark matter halos is well-described by a double power law known as the NFW profile (Navarro et al 1997), an approximation that remains reasonably accurate across most of cosmic time (although see Ludlow et al 2013, for shortcomings of this approximation). Although the concentration parameter that defines the NFW profile exhibits a well-known dependence upon total mass (e.g., Diemer & Kravtsov 2015;Child et al 2018), all halos in the fast-accretion phase tend to have similar values of concentration c ≈ 3 − 4 (Zhao et al 2003a), and as halos transition to the slow-accretion E-mail:ahearin@anl.gov phase, their concentrations steadily increase as they predominantly pile up mass onto their outskirts (see Wang et al 2020, for a detailed physical picture of the relationship between halo assembly and NFW concentration).…”
Section: Introductionmentioning
confidence: 99%
“…To estimate age observationally, we need a structural proxy for age (as expressed, say, by the formation epoch 𝑧 50 ). There are several known examples of structural properties that correlate with 𝑧 50 (Wong & Taylor 2012), including concentration (Zhao et al 2003;Wang et al 2020), shape (as a product of major mergers -Drakos et al 2019a), substructure (e.g. Gao et al 2004;Taylor & Babul 2005;Diemand et al 2007), or overall degree of relaxation, as measured by a centre-of-mass offset (Macciò et al 2007;Power et al 2012).…”
Section: Observational Prospectsmentioning
confidence: 99%